Autonomous Surveillance Robot for Enhanced Security - Abdul Rahman, Zubaidah; Tuan Mohd Yasin, Sharifah Nurulhuda; Mohd Asrol, Muhammad Farish Idlan (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2025)
The need for advanced surveillance systems has increased in recent years, reflecting the growing need for increased security measures in a variety of areas, including public safety, industrial monitoring, and military activities. This abstract proposes the development and execution of an autonomous surveillance robot equipped with cutting-edge technologies to improve security monitoring capabilities. By integrating a variety of sensors, such as motion detectors, infrared sensors, and cameras, the suggested surveillance robot is able to precisely and accurately sense its surroundings. With the use of artificial intelligence algorithms, the robot can detect and monitor several targets, navigate through complex areas on its own, and recognize suspicious activity in real time. One of the surveillance robot's primary characteristics is its strong mobility, which enables it to move across a variety of surfaces, including both indoor and outdoor ones. In addition, the robot is built to function well in a range of weather scenarios, guaranteeing continuous observation capabilities. All things considered, the suggested autonomous surveillance robot is a noteworthy development in security technology, providing better situational awareness, faster reaction times, and increased surveillance capabilities, all of which eventually raise the general level of safety and security in both public and private areas.